(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines the structural relationship between creative competence and the cultivation of creative thinking within the primary education tier. In an era defined by rapid technological shifts, the traditional pedagogical emphasis on rote memorization is being superseded by a need for cognitive flexibility and innovation. This research investigates the terminological nuances of "creative competence" as a prerequisite for "creative thinking," arguing that the former provides the necessary scaffolding for the latter. Through an extensive literature review and discussion on pedagogical implementation, the paper asserts that developing these attributes in early childhood is fundamental for long-term academic resilience and 21st-century problem-solving.